1991
DOI: 10.1007/bf00305309
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of litholytic ethylenediaminetetraacetic acid solutions to the urothelium of the rat and dog

Abstract: The toxicity to the urothelium of bipotassium ethylene-diaminetetraacetic acid (K2-EDTA) buffered with 0.2 M triethanolamine (TEA) at pH 8 and 8.5 was tested in rats and dogs. Even at a low concentration of 3.125 mM, K2-EDTA is very noxious to the bladder mucosa. This toxicity is not due to the buffer TEA, which is well tolerated. Although buffered K2-EDTA, at pH 8.5 is an excellent chemolytic agent for calcium-containing stones, its clinical use is limited by this toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…11 It is also approved for oral use in treating heavy metal intoxication. 12 Some groups 13,14 reported urothelial toxicity when using EDTA intravesically. However, these studies differed from our own as they used EDTA at higher concentrations and higher pH values, and the EDTA was administered for prolonged periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…11 It is also approved for oral use in treating heavy metal intoxication. 12 Some groups 13,14 reported urothelial toxicity when using EDTA intravesically. However, these studies differed from our own as they used EDTA at higher concentrations and higher pH values, and the EDTA was administered for prolonged periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium chelating agents such as EDTA were toxic to the urothelium (Oosterlinck et al 1992) due to the calcium-binding mechanism itself. Dipotassium EDTA buffered with triethanolamine (TEA; pH 8 to 8.5) induced severe lesions to the urothelium of the rat and dog, such that erosion of <20% to >80% of the urothelium was observed (Oosterlinck et al 1991). At a concentration of 3.125 mM, Dipotassium EDTA caused severe lesions of the urinary bladder mucosa; slow perfusion rates and alternating treatment with physiological solution did not decrease the toxicity (Verplaetse et al 1985(Verplaetse et al , 1986.…”
Section: Effects On Mucosamentioning
confidence: 99%
“…Our study also addresses the safety of the infusion of this formulation of 2% tEDTA. Other studies have found that various other forms of EDTA potentially caused urothelial damage in a variety of animal models . In these studies, the urinary tract was intermittently infused with various EDTA formulations for 6 to >20 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In over 260 patients evaluated, over 50% had complete dissolution of their stones (146/260 patients) . Other studies using various solutions containing EDTA suggested potential topical urothelial toxicity . As a result, EDTA irrigation techniques for chemolysis of calcium stones were never adopted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation